The Proposed Elements of Intercultural Communicative Competence (ICC) For Indonesian EFL English Teachers - Mas Muhammad Idris (SAGA: Journal of English Language Teaching and Applied Linguistics, 2021)
The development of intercultural communicative competence (henceforth ICC) has inevitably made one be able to mingle and communicate effectively and appropriately using the target language with other people who have different backgrounds of culture, language, and nation. It is due to the ICC is seen as a complex competence in this twenty-first-century life. However, in the educational context, this competence is rarely noticed seriously by the Indonesian EFL or English teachers. Therefore, this paper is set out to present a comprehensive understanding of ICC and recommend a number of competencies related to ICC that should be possessed by the Indonesian EFL or English teachers in Indonesia. The competencies are linguistic, sociolinguistic, discourse, intercultural competence, and intercultural awareness which are all considered able to assist the Indonesian EFL or English teachers in developing their intercultural competence and their student’s ICC too.